Adaptation of the in vitro micronucleus assay for genotoxicity testing using 3D liver models supporting longer-term exposure durations - Conway, Gillian E; Shah, Ume-Kulsoom; Llewellyn, Samantha; Cervena, Tereza; Evans, Stephen J; Al Ali, Abdullah S; Jenkins, Gareth J; Clift, Martin J D; Doak, Shareen H (Mutagenesis, 2020)
Following advancements in the field of genotoxicology, it has become widely accepted that 3D models are not only more physiologically relevant but also have the capacity to elucidate more complex biological processes that standard 2D monocultures are unable to. Whilst 3D liver models have been developed to evaluate the short-term genotoxicity of chemicals, the aim of this study was to develop a 3D model that could be used with the regulatory accepted in vitro micronucleus (MN) following low-dose, longer-term (5 days) exposure to engineered nanomaterials (ENMs). A comparison study was carried out between advanced models generated from two commonly used liver cell lines, namely HepaRG and HepG2, in spheroid format. While both spheroid systems displayed good liver functionality and viability over 14 days, the HepaRG spheroids lacked the capacity to actively proliferate and, therefore, were considered unsuitable for use with the MN assay. This study further demonstrated the efficacy of the in vitro 3D HepG2 model to be used for short-term (24 h) exposures to genotoxic chemicals, aflatoxin B1 (AFB1) and methyl-methanesulfonate (MMS). The 3D HepG2 liver spheroids were shown to be more sensitive to DNA damage induced by AFB1 and MMS when compared to the HepG2 2D monoculture. This 3D model was further developed to allow for longer-term (5 day) ENM exposure. Four days after seeding, HepG2 spheroids were exposed to Zinc Oxide ENM (0-2 µg/ml) for 5 days and assessed using both the cytokinesis-block MN (CBMN) version of the MN assay and the mononuclear MN assay. Following a 5-day exposure, differences in MN frequency were observed between the CBMN and mononuclear MN assay, demonstrating that DNA damage induced within the first few cell cycles is distributed across the mononucleated cell population. Together, this study demonstrates the necessity to adapt the MN assay accordingly, to allow for the accurate assessment of genotoxicity following longer-term, low-dose ENM exposure.
Keywords: buněčné sféroidy; játra; Humans; mikrojaderné testy; Aflatoxin B1; aflatoxin B1; Models, Biological; Micronucleus Tests; Mutagens; lidé; Hep G2 Cells; buněčné linie; Spheroids, Cellular; Liver; Cell Line; buňky Hep G2; methylmethansulfonát; biologické modely; Hepatocytes; Cell Culture Techniques; mutageny; Methyl Methanesulfonate; hepatocyty; buněčné kultury